Generation Of Expressed Sequence Tags (Ests) From Non-Embryogenic Callus Cdna Libraries Of Oil Palm (Elaeis Guineensis Jacq.) - Tan, Amos Chi Yee (2003)
Due to the economic importance of tissue culture in oil palm, it is desirable to understand the chemical characteristics and molecular changes associated with callogenesis and embryogenesis. Therefore partial sequencing of randomly selected complementary DNA (cDNA) clones was carried out to investigate and understand the gene expression pattern during non-embryogenic callus in oil palm. A total of 2,296 clones from cDNA libraries constructed using messenger RNA (mRNA) from nonembryogenic callus tissues have been partially sequenced to generate expressed sequence tags (ESTs). The comparison of the coding capacity of these 1 ,832 ESTs with the nonredundant sequences in the National Center for Biotechnology Information (NCBI) databases resulted in assignment of putative function to 971 (53.0%) of the ESTs. The remaining 861 (47.0%) were considered as novel genes. Hybridization of the 80 selected cDNA clones to 32P-Iabelled first strand cDNA probes synthesized from the total mRNA of NEC was compared with probes prepared from mRNA of leaves. A total of 1 2 clones, which hybridized predominantly to the NEC but not to the leaf probe were selected for Northern analysis.The Northern analysis showed that 9 out of the 12 ESTs clones selected were expressed predominantly in the callus tissue. However, carrying out a sequence comparison using the BLAST algorithm, only l out of the 9 clones had significant homology to a known gene, glutathione-S-transferase (GST) gene. The remaining 8 unidentifiable ESTs were then subjected to a motif search using the Blocks IMProved Searcher (BLIMPS) program. Based on the search results, 4 different motifs were identified to be related to the 8 ESTs and they are either involved in developmental regulation or protein storage function. The results presented here therefore demonstrate the effectiveness and efficiency of the EST strategy in gene discovery in the oil palm callus tissue.